PENGGUNAAN MEDIA FIND THE MATCH WORD WOLL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - patimah; Iis Nurasiah; Din Azwar Uswatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the use of Find The Match Word Wall media to improve the early reading skills of elementary school students. This study was conducted at Kadudampit Elementary School, Sukabumi Regency, West Java. Participants in the study were 32 students. The research method used was classroom action research with the Kemmis and Mc Taggart research design model, which was carried out in two cycles. Each cycle consisted of planning, implementation, action and observation, and reflection. Data collection techniques used initial reading practice tests, and non-tests in the form of observation, field notes, and documentation. The data analysis technique used was qualitative. The improvement of early reading skills after applying Find The Match Word Wall media was seen from the results of observations of teacher activities, on average, cycle I obtained a score of 75 in the sufficient category and cycle II 83 in the good category. Observations of student activities obtained a score of 72 in the sufficient category in cycle I and 81 in the good category in cycle II, this indicates an improved learning process using word wall media. The percentage of pre-cycle completion was 34%, cycle I was 69%, and cycle II was 81%. And it has been proven that implementing Find the Match Word Word can improve the early reading skills of elementary school students in phase A (first grade). Keywords: Find the Match Word Word Word, Early Reading, Elementary School